Policy Model Structure in Anthrax Prevention: A One-Health Approach at the Cross-Border Regional Level - Handika, Denis Oxy; Hasanbasri, Mubasysyir (BKM Public Health and Community Medicine, 2024)
Purpose: The results of the investigation of anthrax outbreaks in the provinces of Yogyakarta and East Java over the past five years indicate an epidemiological link. The high trade of livestock and meat products between regions is one of the risk factors. Therefore, it is essential to gain a deeper understanding of the ecological dynamics and pandemic potential of zoonotic diseases, along with cross-regional program coordination to respond to emergency situations, maintain public health, and minimize the negative impacts on a broader scale. Method: A logical framework model was utilized in the context of anthrax prevention and control initiatives. Significance was placed on formulating strategies that prioritize the efficiency, effectiveness, and sustainability of the program, aligning with its specific objectives. Results: The commitment of the Cross-Regional Anthrax Control Team, which involves elements of the Regional Government, Health Office, Agriculture and Livestock Service Office, Public Health Laboratory Center, Veterinary Center, research and development centers, non-governmental organizations (NGOs) and beneficiary communities, is an important element in ensuring the sustainability of the program. The implementation of the One-Health-based program, training for farmers and animal traders to recognize signs of anthrax, as well as routine animal health checks, are efficient steps in the program process to strengthen the surveillance system that supports the early warning system, and improve the capacity of farmers and animal traders to detect anthrax symptoms and report them to the authorities. Thus, the program objectives in anthrax control can be effectively achieved, to reduce the number of anthrax cases, prevent its spread, reduce economic losses, and increase public confidence in food safety. Conclusion: The implementation of this concept will enable the establishment of a cross-regional One-Health-based anthrax control program that is sustainable, efficient, and effective in addressing anthrax in the provinces of Yogyakarta and East Java.